SDO Cagayan's Training Platforms: A Comparative Analysis of Social Presence, Interaction, Collaborative Learning, and Satisfaction - Andrew Toribio B. Taaca; Rex Angel Asuncion; Kevin D. Caratiquit (Journal of Social, Humanity, and Education, 2026)
Purpose: This study examined teachers' assessments of online and face-to-face training platforms in the Schools Division Office (SDO) of Cagayan, Philippines, across four dimensions: social presence, social interaction, collaborative learning, and satisfaction. Methodology: This study used a mixed methods sequential explanatory design and involved 388 teachers selected through proportional stratified random sampling. Survey data and qualitative responses from interviews and open?ended questions were analyzed to compare perceptions across training modes, Results: Results showed consistently higher ratings for face-to-face training across all four dimensions, with significant differences favouring in-person interactions. Teachers highlighted stronger interpersonal connections, more effective collaboration, and greater overall satisfaction in face-to-face settings, while acknowledging the accessibility and flexibility of online platforms. Several profile variables, such as ICT skill level and prior training, significantly influenced perceptions. Both modalities presented unique challenges, including engagement and scheduling issues in face-to-face training and device or connectivity issues in online training. Conclusions: This study compared teachers' perceptions of face-to-face and online training. Face-to-face training scored higher in social presence, interaction, and collaboration. Despite the flexibility of online training, it faced challenges. The results suggest that a blended approach would be more effective for teacher development. Limitations: This study focused on teachers' perceptions during SY 2022–2023 and relied primarily on self-report data from an adapted instrument. Contributions: The findings informed the development of policy recommendations to strengthen the implementation of both online and face-to-face training programs.